Association of Serum Uric Acid and Metabolic Syndrome in Type 2 Diabetes - Bonakdaran, Shokoufeh; Kharaqani, Banafsheh (Current Diabetes Reviews, 2014)
Aim: The relationship between elevated serum uric acid level and metabolic syndrome (MS) has been debated. There is no data concerning this relation in Iranian population-based studies. The aim of this study was to determine the prevalence of hyperuricamia and its association with MS in type 2 diabetes mellitus (DM). Patients and Methods: This was a cross- sectional study in 1978 diabetic patients. Hyperuricamia was defined as uric acid ≥ 7 and ≥ 5.5 mg/dl for men and women respectively. Diagnosis of metabolic syndrome was based on ATPIII criteria. Clinical and biochemical parameters in hyperuricaemic and normouricaemic patients compared with other. Results: The prevalence of hyperuricaemia and metabolic syndrome was 12.7% and 65.5% respectively. The prevalence of MS significantly increased in the highest quartile of uric acid levels compared with lowest quartile (74.4% vs 55.9%, p<0.001). Serum uric acid had positive association with cholesterol, triglyceride, non-HDL cholesterol and a negative association with fasting blood sugar (FBS), glycosylated hemoglobin (HbA1C) and HDL cholesterol. Possible independent biochemical predictors of hyperuricamia were cholesterol, triglyceride, creatnine and FBS. Conclusion: The prevalence of MS and its components increases with increasing levels of uric acid in type 2 diabetes. Regular assessment of uric acid could give information for predicting of MS and prevention of atherosclerosis in type 2 diabetes.
Keywords: insulin resistance